The Role of Agroforestry on Food Security and Climatefriendly Farming in Nepal and its Challenges and Approaches - Dahal, Rudra Nath (BARUN Journal, 2024)
The integration of forestry with agriculture, known as agroforestry, is a longstanding practice that incorporates trees into farming systems and landscapes. Unlike a substitute technique, agroforestry complements traditional agricultural methods. Climate change presents global challenges, particularly impacting the agricultural sectors of developing nations. Climate Smart Agriculture (CSA), introduced by the Food and Agricultural Organization (FAO) in 2010, offers a sustainable alternative to conventional farming by aiming to reduce greenhouse gas emissions while enhancing agricultural productivity, resilience, and efficiency. This review explores the role of agroforestry in promoting food security and climate-friendly farming, identifies challenges hindering its adoption, and proposes strategies to enhance implementation. By fostering sustainable development and improving rural livelihoods, agroforestry contributes significantly to climate change resilience. The study employs a qualitative research design, synthesizing secondary sources to analyze agroforestry practices, challenges, and contributions. Agriculture accounts for up to 14 percent of greenhouse gas emissions, while deforestation and erosion contribute an additional 17 percent. Climate-friendly agriculture, rooted in sustainable practices, focuses on increasing agricultural production and income sustainably, adapting to climate change, and reducing greenhouse gas emissions. By promoting climate-friendly agriculture in Nepal, local knowledge and resources can be effectively utilized, generating self-employment opportunities, reducing production costs, and promoting sustainable agricultural ecosystems. Implementing climate-friendly agriculture is crucial for achieving sustainable development goals and mitigating the adverse effects of climate change in agricultural systems.